PARARELISME DALAM DOU SANDIK GUYUB TUTUR BIAK NUMFOR-PAPUA - WARAMI, HUGO (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2007)
Abstract The speech community of Biak Numfor represents one community which are using the same language variant as a socio cultural media and also as distinguishing feature in facing their every day reality of life as well as as a carrier of set of norm and rules which is same in form of language. Every form of parallelism it?s a fair sharing between unchanging elements and changing elements. More tide of the distribution of unchanging elements, its getting more big differences and variation effectiveness. Parallelism in the text of Dou Sandik GTBN will be explained base on procedure which proposed by Jacobson , which are unchanging elements and changing elements which aim to specify repetition and existing parallels. Kata Kunci: Paralelisme, Dou Sandik, dan Guyub Tutur